2002
DOI: 10.1128/iai.70.4.2108-2120.2002
|View full text |Cite
|
Sign up to set email alerts
|

Specific Entry ofHelicobacter pyloriinto Cultured Gastric Epithelial Cells via a Zipper-Like Mechanism

Abstract: Although Helicobacter pylori has generally been considered an extracellular pathogen, a number of in vitro infection experiments and biopsy examinations have shown that it is capable of occasionally entering mammalian host cells. Here, we characterized this entry process by using AGS cells as a host cell model. In gentamicin protection-invasion assays, the number of H. pylori colonies recovered was lower than that for Salmonella enterica serovar Typhimurium X22, Escherichia coli expressing InvA, and Yersinia e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
126
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(137 citation statements)
references
References 94 publications
9
126
1
1
Order By: Relevance
“…Previous studies of a gastric adenocarcinoma-derived cell line revealed internalized H. pylori within Lamp1-containing vacuoles, suggesting that cellular entry may occur via zipper-like receptor-mediated endocytosis, as occurs with Yersinia pseudotuberculosis, Yersinia enterocolitica, Neisseria gonorrhoeae and Listeria monocytogenes infections (21). In the latter infections, intracellular bacteria located within vacuolar compartments use several different mechanisms to prevent maturation of host cell phagosomes (i.e., their fusion to lysosomes), including alterations in the composition of the phagosomal membrane and segregation from the endocytic pathway.…”
Section: Tem Studies Of Geps Harboring H Pylorimentioning
confidence: 99%
“…Previous studies of a gastric adenocarcinoma-derived cell line revealed internalized H. pylori within Lamp1-containing vacuoles, suggesting that cellular entry may occur via zipper-like receptor-mediated endocytosis, as occurs with Yersinia pseudotuberculosis, Yersinia enterocolitica, Neisseria gonorrhoeae and Listeria monocytogenes infections (21). In the latter infections, intracellular bacteria located within vacuolar compartments use several different mechanisms to prevent maturation of host cell phagosomes (i.e., their fusion to lysosomes), including alterations in the composition of the phagosomal membrane and segregation from the endocytic pathway.…”
Section: Tem Studies Of Geps Harboring H Pylorimentioning
confidence: 99%
“…PI3Ks modulate many cytoskeleton-based cellular processes, including adhesion, spreading, macropinocytosis, and phagocytosis. PI3K has been shown to be necessary for the invasion of epithelial cells by several bacteria, including Listeria monocytogenes (Ireton et al, 1996), Helicobacter pylori (Kwok et al, 2002), and Escherichia coli K1 (Reddy et al, 2000).Both PtdIns(3,4)P 2 and PtdIns(3,4,5)P 3 have been shown to activate one of the main downstream targets of PI3K, the serine threonine protein kinase B (PKB), also known as Akt (Burgering and Coffer, 1995;Vanhaesebroeck and Alessi, 2000). On binding to phosphoinositides by its PH domain, Akt is recruited to the membrane where it is phosphorylated by PDK1 at threonine 473 and at serine 308, leading to activation of its kinase activity.…”
mentioning
confidence: 99%
“…Both PI3-K and PKC are required for bacterial uptake and induction of cytoskeletal rearrangements [30]. Curiously preinfection of cultured gastric cells with yersinia expressing Yop virulence factors that interfere with the same signaling events impaired phagocytosis of H. pylori [30]. Internalized H. pylori was shown to be located in tight phagosomes and in close association with condensed actin filaments and localized tyrosine phosphorylation signals.…”
Section: Induced Phagocytosis By Invasive Pathogensmentioning
confidence: 99%
“…In all cases, however, invasion of H. pylori seems to involve a typical zipper-like entry process. Both PI3-K and PKC are required for bacterial uptake and induction of cytoskeletal rearrangements [30]. Curiously preinfection of cultured gastric cells with yersinia expressing Yop virulence factors that interfere with the same signaling events impaired phagocytosis of H. pylori [30].…”
Section: Induced Phagocytosis By Invasive Pathogensmentioning
confidence: 99%